2D WS2 liquid crystals: tunable functionality enabling diverse applications. Issue 36 (4th September 2019) - Hogan, Benjamin T.; Kovalska, Evgeniya; Zhukova, Maria O.; Yildirim, Murat; Baranov, Alexander; Craciun, Monica F.; Baldycheva, Anna
Abstract : A liquid crystal state has been observed for dispersions of tungsten disulfide in various organic solvents, allowing the creation of highly uniform thin films whose wide-ranging applicability is explored. Abstract : The first observation of liquid crystalline dispersions of liquid phase-exfoliated tungsten disulfide flakes is reported in a range of organic solvents. The liquid crystals demonstrate significant birefringence as observed in the linear and circular dichroism measurements respectively. In particular, linear dichroism is observed throughout the visible range while broad-band circular dichroism can be observed in the range from 500–800 nm. Under an applied magnetic field of ±1.5 T the circular dichroism can be switched ON/OFF, while the wavelength range for switching can be tuned from large to narrow range by the proper selection of the host solvent. In combination with photoluminescence capabilities of WS2, this opens a pathway to a wide variety of applications, such as deposition of highly uniform films over large areas for photovoltaic and terahertz devices.